2022
DOI: 10.30998/ocim.v2i2.8130
|View full text |Cite
|
Sign up to set email alerts
|

Resiliensi akademik siswa

Abstract: academic resilience is one component of self that needs to be owned by every student in the face of academic pressure. Uniquely, not all students have optimal academic resilience. This study aims to determine the description of students' academic resilience. This research is a descriptive quantitative research. The population in this study was 204 students. Samples were drawn randomly by determining the magnitude using the Slovin formula at a significance level of 0.05. Through this formula, the number of samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…found that students' academic resilience tends to be low, from the results of distributing a questionnaire to 80 students out of 372 class X MM SMK IBU students . Other research showing low resilience was conducted by (Irawan et al, 2022) from 135 research samples it was found that 17 (12.59%) students had a low level of academic resilience. Likewise, the results of research conducted by Meiranti & Sutoyo (2021) show that as many as 47 students out of 170 vocational school students with a percentage of 28% have low academic resilience.…”
Section: Introductionmentioning
confidence: 94%
“…found that students' academic resilience tends to be low, from the results of distributing a questionnaire to 80 students out of 372 class X MM SMK IBU students . Other research showing low resilience was conducted by (Irawan et al, 2022) from 135 research samples it was found that 17 (12.59%) students had a low level of academic resilience. Likewise, the results of research conducted by Meiranti & Sutoyo (2021) show that as many as 47 students out of 170 vocational school students with a percentage of 28% have low academic resilience.…”
Section: Introductionmentioning
confidence: 94%